Correlação entre dor e polimorfismo do gene COMT em pacientes com deformidade dentofacial submetidos à cirurgia ortognática - Meger, Michelle Nascimento (2017)
Introduction: Temporomandibular dysfunction (TMD) can be defined as a masticatory system disorder. One of the main symptoms of TMD is pain. Skeletal discrepancies are considered risk factors for the development of TMD. Objective: The objective of this study was to investigate whether there is an association between temporomandibular pain with clinical and genetic variables in patients with dentofacial deformity. Materials and Methods: 145 patients were evaluated for TMD signs and symptoms through the Research Diagnostic Criteria for Temporomandibular Disorders (RDC / TMD). For genetic evaluation, COMT (Catechol-O-Methyltransferase) gene markers were selected, which is associated with the pain outcome. The rs4818 and rs6269 markers were genotyped using the real-time PCR technique. Data were submitted to statistical analysis, with significance level of 0.05. Results: Women are more likely to have temporomandibular pain than men (p = 0.023). Patients with temporomandibular pain had lower mouth opening (p = 0.05), more chronic pain (p < 0.001), more depression (p = 0.03) and more pain somatization (p = 0.022). According to the gender-adjusted multinomial regression, it was possible to observe in the additive model of the rs6269 marker that homozygous A individuals are 2.46 times more likely to present pain when compared to G homozygotes (p = 0.03). Conclusion: Women with dentofacial deformity present more chronic pain, more symptoms of depression and more somatization of pain. In addition, homozygous A subjects have a greater predisposition to pain than homozygous individuals G, for the rs6269 marker.